Pollinator Behavior Drives Sexual Specializations in the Hermaphrodite Flowers of a Heterodichogamous Tree - Wajnberg, Eric; Tel-Zur, Noemi; Shapira, Idan; Lebber, Yochai; Lev-Yadun, Simcha; Zurgil, Udi; Reisman-Berman, Orna; Keasar, Tamar (Frontiers in Plant Science, 2019)
Dioecy, the specialization of individuals into either male-only or female-only sexual function, has multiple evolutionary origins in plants. One proposed ancestral mating system is heterodichogamy, two morphs of cross-fertilizing hermaphrodite flowers that differ in their timing of flowering. Previous research suggested that small specializations in these morphs’ functional genders could facilitate their evolution into separate sexes. We tested the possible role of pollinators in driving such specializations. Ziziphus spina-christi is an insect-pollinated heterodichogamous tree with self-incompatible flowers and two sympatric flowering morphs. We compared the flower development patterns, floral food rewards, pollinator visits and fruit production between the two morphs. Male-phase flowers of Z. spina-christi’s “Early” and “Late” morphs open before dawn and around noon, respectively, and transition into female-phase 7-8 hours later. Flowers of both morphs contain similar nectar and pollen rewards, and receive visits by flies (their ancestral pollinators) at similar rates, mostly during the morning. Consequently, the Early morph functions largely as pollen donor. The Late morph, functioning as female in the morning, produces more fruit. We developed an evolutionary probabilistic model, inspired by Z. spina-christi’s reproductive system, to test whether pollinator visit patterns could potentially play a role in an evolutionary transition from heterodichogamy towards dioecy. The model predicts that reproductive incompatibility within flowering morphs promotes their evolution into different sexes. Furthermore, the pollinators’ morning activity drives the Early and Late morphs’ specialization into male and female functions, respectively. Thus, while not required for transitioning from heterodichogamy to dioecy, pollinator-mediated selection is expected to influence which sexual specialization evolves in each of the flowering morphs.